2000
DOI: 10.1007/s000660050006
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current and Future Treatment Strategies for Malignant Astrocytomas in Adults

Abstract: Several rational new approaches are now entering clinical trials (Table 2). In the light of limited survival after standard treatment it is recommended that patients should be offered participation in such trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
7

Year Published

2001
2001
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 62 publications
1
9
0
7
Order By: Relevance
“…The present study revealed age, neurological performance scale, addition of radiotherapy and extend of resection as prognostic factors at multivariate analysis, which is in agreement with other publications on prognostic factors [2,4,16,17,27]. In this study a total or nearly total resection according to the statement of the neurosurgeon was of prognostic value.…”
Section: Tabelle 3 Multivarianzanalyse Von Prognosefaktoren (Cox-regsupporting
confidence: 80%
See 2 more Smart Citations
“…The present study revealed age, neurological performance scale, addition of radiotherapy and extend of resection as prognostic factors at multivariate analysis, which is in agreement with other publications on prognostic factors [2,4,16,17,27]. In this study a total or nearly total resection according to the statement of the neurosurgeon was of prognostic value.…”
Section: Tabelle 3 Multivarianzanalyse Von Prognosefaktoren (Cox-regsupporting
confidence: 80%
“…Considering the limited survival with standard treatments it is recommended to enter glioblastoma patients in trials investigating new alternative strategies, based on recent advances in our knowledge about the biology of malignant gliomas [16]. At fundamental level we are currently investigating the cellular kinetics of malignant gliomas in relation to their genetic aberrations in glioma cell cultures and human glioblastoma multicellular spheroids, in order to individualize treatment in the future.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The late side effects of therapeutic irradiation are significantly higher in patients who received a whole brain irradiation [1,4,5,7,19]. The improvements in tumor localization via CT, MRI and SPECT and better treatment planning made precise limited volume irradiation feasible in the last decade [16,22].…”
Section: Discussionmentioning
confidence: 99%
“…In den untersuchten Jahrgängen gab es 14 Publikationen mit nur einem einzigen Autor [21,36,38,66,69,80,86,88,100,111,117,135,141,158]. Insgesamt 20 Publikationen hatten zwei Autoren [8,9,28,37,50,65,78,103,109,114,116,123,124,148,149,150,151,157,163,164], 21 Publikationen drei Autoren [6,20,35,40,41,42,43,52,70,73,74,75,112,122,126,127,132,…”
Section: Analyse Der Zeitschrift "Strahlentherapie Und Onkologie" (Jaunclassified